REPRESENTASI NILAI AKHLAKUL KARIMAH DALAM SERI MENELADANI SIFAT DAN KARAKTER RASULLULLAH - Awliya Rahmi (Universitas Terbuka, 2023)
This study aims to explain the nature and character of the Holy Prophetsa as narrated in the series Children's Books Exemplifying the Nature and Character of the Prophet published by Ziyadbooks. This research method is carried out with a qualitative approach by applying the content analysis method. The results of the analysis show that to achieve the purpose of conveying the nature and character of the Holy Prophetsa to children, the narrative used in this book is in the form of short and simple sentences. The form of narration used to explain the nature and character of the Holy Prophet in this book is in the form of descriptive and dialogue. Based on this, it can be concluded that the age and cognitive development of children as readers are the main considerations in the selection of vocabulary and sentence construction used in this book.